Odpowiedź :
Odpowiedź:
[tex]\dfrac{ (2log_{3}4+4log_{3}1,5)\cdot (log_{0,5}50-2log_{0,5}5) }{log_{\sqrt{5} } 4 -2log_{\sqrt{5} } 10 } =\dfrac{4\cdot (-1)}{(-4)} =1[/tex]
Szczegółowe wyjaśnienie:
Osobno obliczę wrażenia w nawiasach:
[tex]I.\\\\2log_{3} 4+4log_{3} 1.5=2log_{3} 4+4log_{3} \frac{3}{2} =log_{3} 4^{2} +log_{3} (\frac{3}{2} )^{4} =log_{3} 16+log_{3} \frac{81}{16} =log_{3} (16\cdot \frac{81}{16} )=log_{3} 81=log_{3} 3^{4} =4log_{3}3=4\cdot 1=4\\\\\\\\II.\\\\log_{0,5} 50 - 2log_{0,5} 5 =log_{0,5} 50 - log_{0,5} 5^{2} =log_{0,5} 50 - log_{0,5} 25 =log_{00,5} (50\div 25)=log_{0,5} 2=log_{0,5} 0,5^{-1} =-1log_{0,5} 0,5 =-1\cdot 1=-1\\\\\\[/tex]
[tex]III.\\\\log_{\sqrt{5} } 4 -2log_{\sqrt{5} } 10=log_{\sqrt{5} } 4 -log_{\sqrt{5} } 10^{2} =log_{\sqrt{5} } 4 -log_{\sqrt{5} } 100=log_{\sqrt{5} } 4\div 100=log_{\sqrt{5} } \frac{1}{25} =log_{\sqrt{5} } 25^{-1} =log_{\sqrt{5} } 5^{-2} =-4\\\\loog_{\sqrt{5} } 5^{-2} =x~~\Leftrightarrow ~~(\sqrt{5}) ^{x} =5^{-2} \\\\(\sqrt{5}) ^{x} =5^{-2} \\\\(5^{\frac{1}{2} } ) ^{x} =5^{-2} ~~\Leftrightarrow ~~~\dfrac{1}{2} x=-2~~\Rightarrow ~~x=-4[/tex]
Podstawiam:
[tex]\dfrac{ (2log_{3}4+4log_{3}1,5)\cdot (log_{0,5}50-2log_{0,5}5) }{log_{\sqrt{5} } 4 -2log_{\sqrt{5} } 10 } =\dfrac{4\cdot (-1)}{(-4)} =1[/tex]
Korzystam ze wzorów:
[tex]log_{a} a=1\\\\log_{a} b + log_{a} c =log_{a} (b\cdot c)\\\\log_{a} b - log_{a} c =log_{a} (b\div c)\\\\xlog_{a}b =log_{a} b^{x}\\\\log_{a}b=c~~\Leftrightarrow ~~a^{c} =b[/tex]